The Actin Regulators Involved in the Function and Related Diseases of Lymphocytes - Sun, Jianxuan; Zhong, Xingyu; Fu, Xiaoyu; Miller, Heather; Lee, Pamela; Yu, Bing; Liu, Chaohong (Frontiers in Immunology, 2022)
Actin is an important cytoskeletal protein that is involved in several biological intracellular activities including signaling transduction, morphological maintenance and motility. Actin regulators, including actin-monomer-binding proteins, Wiskott-Aldrich syndrome (WAS) family of proteins, nucleation proteins, actin filament polymerases, severing proteins are a group of proteins which regulate the dynamic changes in actin assembly/disassembly, and thus play an important role in cell motility, intracellular transport, cell division and other basic cellular activities. Lymphocytes are important components of the human immune system, consisting of T-lymphocytes (T cell), B-lymphocytes (B cell) and natural killer cells (NK cell). Lymphocytes are indispensable for both innate and adaptive immunity and cannot function normally without various actin regulators. In this review, we first briefly introduce the structure and fundamental functions of a variety of well-known and newly found actin regulators, then we highlight the role of actin regulators in T cell, B cell and NK cell, and finally we provide a landscape of various diseases associated with them. This review can provide possible new directions in studying actin regulators and promote more precise and effective treatments for related diseases.